Do behavioural interventions enhance waste recycling practices? Evidence from an extended meta-analysis. (20th January 2023) - Xia, Ziqian; Gu, Yanjun; Li, Jiangnan; Xie, Jinliang; Liu, Fangyi; Wen, Xing; Tian, Xi; Zhang, Chao
Abstract: Recycling behaviours are essential for improving resource efficiency and reducing environmental pollution caused by waste disposal. Behavioural interventions, as low-cost and effective nonregulatory approaches, have been widely used to promote recycling. In this paper, we comprehensively evaluate the effect of behavioural interventions through a preregistered meta-analysis (a total of 206 effect sizes were collected, covering 1167, 069 samples). We find that, overall, interventions have small to moderate effects ( Fisher's z = 0.195; 95% CI 0.141, 0.249). Among the different approaches, education, environmental alteration and campaign interventions can achieve better effects ( Fisher's z ≥ 0.2), while incentives and commitment have weaker effects ( Fisher's z < 0.2). The duration and context of the intervention had no significant effects (p < 0.1). We emphasize the need for behavioural interventions to highlight the role of social interactions and to enhance waste recycling practices.